2013
DOI: 10.13080/z-a.2013.100.005
|View full text |Cite
|
Sign up to set email alerts
|

Soil compaction in a Cambisol under grassland in Estonia

Abstract: In soil compaction research, more attention has been given to arable land than to grasslands. Our objective was to investigate the effect of agricultural machinery on the physical and mechanical properties of soil under intensively cut lucerne (Medicago sativa L.). A field experiment was conducted in South Estonia, near the city of Tartu, on a second-year mainly lucerne field on a sandy loam Calcaric Cambisol (CMca). After the third silage cut, soil properties were measured in the wheel traffic lanes (compacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In this context, organic soils with a fine pore structure are more vulnerable to compaction under mowing in comparison with sandy soils (Schrama, Cordlandwehr, et al, 2013). Soil compaction increases soil bulk density, and pre-compression stress, decreases soil air capacity, the percentage soil porosity, air conductivity, soil water content, root distribution, and hydraulic conductivity (Batey, 2009;Krebstein et al, 2013Krebstein et al, , 2014Schrama, Cordlandwehr, et al, 2013). Moreover a high range of soil pores in compacted soils would fill with water thus the potential of soil redox and the oxygen diffusion in soil pore space would be decreased (Schrama, Cordlandwehr, et al, 2013).…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
“…In this context, organic soils with a fine pore structure are more vulnerable to compaction under mowing in comparison with sandy soils (Schrama, Cordlandwehr, et al, 2013). Soil compaction increases soil bulk density, and pre-compression stress, decreases soil air capacity, the percentage soil porosity, air conductivity, soil water content, root distribution, and hydraulic conductivity (Batey, 2009;Krebstein et al, 2013Krebstein et al, , 2014Schrama, Cordlandwehr, et al, 2013). Moreover a high range of soil pores in compacted soils would fill with water thus the potential of soil redox and the oxygen diffusion in soil pore space would be decreased (Schrama, Cordlandwehr, et al, 2013).…”
Section: Soil Physical Propertiesmentioning
confidence: 99%
“…Because of compaction, the P c values in the upper soil layer (0−20 cm) increased compared with the uncompacted area. Krebstein et al (2013) found that due to soil compaction, the P c increased in the upper soil layer to 60 kPa and to 30 kPa at a soil depth of 10 cm. According to our results, we can assume that the binding substances are not really changed, hence, the number of contact points must be increased (verified by BD).…”
Section: Resultsmentioning
confidence: 96%
“…Schrama et al (2012) compared different cutting regimes, traditional versus mechanical mowing, on grasslands and showed that long-term (38 years) machine mowing causes compaction, particularly on organic soils. Krebstein et al (2013) showed on sandy loam Calcaric Cambisol under lucerne that soil compaction is also a problem on farm-used grasslands. Because of soil compaction, the soil properties are altered, and a reduction in soil water and roots can occur (Baty 2009).…”
mentioning
confidence: 99%
“…It is usually ascribed to unfavourable changes of soil properties. Soil compaction leads to soil structure degradation, which is strongly associated with changes in physical properties of soil like porosity, bulk density, and penetration resistance (Krebstein et al, 2013;Nawaz et al, 2013). The degraded physical environment of the soil due to compaction influences mainly the growth and development of roots.…”
Section: Discussionmentioning
confidence: 99%